Carlos Heitor Cony: - Leite, Milene Pereira (Universidade Federal do Tocantins, 2023)
This study aims to understand the military dictatorship, through the narratives of the writer Carlos Heitor Cony which promotes resistance to the regime in the book chronicles the Act and the fact that it was published in 1964, the newspaper Correio da Manhã. We will also analyze the role and the concept of intellectual from the call that Cony make these in chronic "The Time of Intellectuals". The Brazilian military regime despised democracy, stripped mandates, arrested, tortured and killed the state's opponents, the military practiced serious violations of human rights, legitimized by the will to provide the National Security, a military movement that according to them, it was a "Revolution".